Asphalt pavements - Kim, Y. Richard (CRC Press/Balkema is an imprint of the Taylor & Francis Group, an infoma business, 2014)
Asphalt Pavements contains the proceedings of the International Conference on Asphalt Pavements (Raleigh, North Carolina, USA, 1-5 June 2014), and discusses recent advances in theory and practice in asphalt materials and pavements. The contributions cover a wide range of topics: - Environmental protection and socio-economic impacts - Additives and modifiers for asphalt concrete - Maintenance and rehabilitation - Experimental characterization of asphaltic materials - Life cycle cost analysis/modeling of compaction in the laboratory and in the field - Perpetual pavements - Pavement management systems - Sustainable asphalt technologies - Nondestructive testing of asphalt pavement - Pavement condition survey/pavement smoothness/quality control/quality assurance - Microstructural characterization and micromechanics of asphaltic materials - Long-term pavement performance prediction - Mineral aggregate in asphalt concrete/mix design methodology/novel methods to aid mix design - Warm mix asphalt technologies - Innovative pavement analysis and design - Pavement response analysis under static and moving wheel loads - Recycling - Modeling of asphaltic materials and pavements - Microstructural characterization and micromechanics of asphalt materials - Asphalt pavement and environment - Performance-related specifications Asphalt Pavements will be of interest to academics and professional involved in asphalt engineering